Viabilitas dan Infektivitas Formulasi Cendawan Entomopatogen Lecanicillium lecanii sebagai Biopestisida Pengendalian Telur Kepik Coklat Riptortus linearis - Prayogo, Yusmani; Santoso, Teguh (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
Lecanicillium lecanii fungi is an effective entomopathogenic fungus to control soybean pod sucking bug. The fungi is able to parasitize spore of pathogens that cause major diseases of soybean, such as rust, downy mildew, and powdery mildew. The study was aimed to determine the 12 formulations that can maintain spore viability and infectivity for 12 months. The formulations used talk, kaolin, sweet potato flour, cassava flour, rice flour, corn flour, soybean flour, mungbean flour, peanut flour, potato flour, molasses, peanut oil, and soybean oil based medium. Each medium was sterilized and mixed individually with conidia suspension of L. lecanii to form powder formulations that contained 107 conidia/ml. The spore viability and infectivity were tested after storing the formulations for twelve months. The result showed that viability and infectivity of spores in the formulation was lower with the longer period of storage. Viability of conidia in the formulation decreased to the lowest 20% after 12 months storage, especially that in peanut powder formulation. The spore viability in the cassava flour formulation was the highest (95%). Infectivity of the L. lecanii formulation using cassava flour to inhibit egg hatching of brown stink bug was 60% after 12 months storage. The viability and infectivity of L. lecanii spores in powder formulation was better than those in liquid formulations.